Effect of Hearing Loss and Simulated Hearing Aid Amplification on Prosody Perception: From Neural Encoding to Behavioral Response - Karimi Boroujeni, Maryam (Université d'Ottawa / University of Ottawa, 2025)
Speech prosody, an essential component of social interaction for conveying emotional information, has been often overlooked in the assessment and management of hearing-impaired individuals. Furthermore, existing literature remains inconclusive on whether hearing loss impairs emotion perception and to what extent hearing aids can compensate for potential deficits in prosody processing. Previous studies have predominantly examined behavioral performance in emotion perception tasks, with limited insight into the neural processing of prosody in normal-hearing and hearing-impaired populations. This study investigated whether the speech-evoked frequency-following response (FFR) can track variations in fundamental frequency (F0 contour) in emotional speech, and to examine male/female differences in the neural encoding of emotional prosody. Additionally, we evaluated the impact of hearing loss and simulated hearing aid processing on the neural representation of F0 contours. To complement electrophysiological measures, the behavioral responses of hearing-impaired individuals were also examined through an emotion identification task conducted under cognitively demanding conditions. We further investigated the association between individuals' ability to perceive prosody and their speech-in-noise perception. First, FFRs were recorded from normal-hearing young adults in response to the word "balloon" spoken by one male and one female talker with sad and happy emotion, and F0 tracking accuracy was calculated. This method was then applied to hearing-impaired individuals (aided and unaided) and age-matched normal-hearing controls using male-spoken "balloon" expressing sad and happy emotions. Afterward, all participants underwent an emotion identification test with a secondary free recall task. The Quick Speech-In-Noise test (QuickSIN) was also conducted to determine participants' SNR loss. The results showed the FFR can track F0 contours in emotional speech, influenced by emotion type and talker voice characteristics but not by listener sex. Hearing loss disrupted neural representation of F0 contours, although amplification could partially restore it. Hearing loss also adversely affected behavioral performance and increased cognitive demands for prosody perception; however, amplification could not fully compensate for this perceptual deficit. Moreover, SNR loss was negatively correlated with emotion identification accuracy. This study emphasized the need to consider prosody perception difficulties in the assessment and rehabilitation of hearing-impaired individuals and suggested the FFR's potential for identifying deficits in prosodic processing.